Using Observations and Source‐Specific Model Tracers to Characterize Pollutant Transport During FRAPPÉ and DISCOVER‐AQ. Issue 19 (12th October 2017) - Pfister, G. G.; Reddy, P. J.; Barth, M. C.; Flocke, F. F.; Fried, A.; Herndon, S. C.; Sive, B. C.; Sullivan, J. T.; Thompson, A. M.; Yacovitch, T. I.; Weinheimer, A. J.; Wisthaler, A.
Abstract: Transport is a key parameter in air quality research and plays a dominant role in the Colorado Northern Front Range Metropolitan Area (NFRMA), where terrain‐induced flows and recirculation patterns can lead to vigorous mixing of different emission sources. To assess different transport processes and their connection to air quality in the NFRMA during the FRAPPÉ and DISCOVER‐AQ campaigns in summer 2014, we use the Weather Research and Forecasting Model with inert tracers. Overall, the model represents well the measured winds, and the inert tracers are in good agreement with observations of comparable trace gas concentrations. The model tracers support the analysis of surface wind and ozone measurements and allow for the analysis of transport patterns and interactions of emissions. A main focus of this study is on characterizing pollution transport from the NFRMA to the mountains by mountain‐valley flows and the potential for recirculating pollution back into the NFRMA. One such event on 12 August 2014 was well captured by the aircraft and is studied in more detail. The model represents the flow conditions and demonstrates that during upslope events, frequently, there is a separation of air masses that are heavily influenced by oil and gas emissions to the north and dominated by urban emissions to the south. This case study provides evidence that NFRMA pollution not only can impact the nearby foothills and mountain areas to the east of the Continental Divide but that pollution can "spillover" into the valleys to the west of the Continental Divide. Key Points: Upslope flows are a frequent occurrence on high ozone days in the NFRMA, thereby impacting remote mountain sites Aircraft measurements and model tracers confirm transport of pollution to the mountains and spillover into the valleys to the west of the Continental Divide The northern foothills are frequently impacted by oil and gas sources, while the southern foothills more frequently experience impact from urban sources